PENTINGNYA WORK ENGAGEMENT, WORK-STUDY CONFLICT DAN WORK-LIFE BALANCE : BAGI KARYAWAN YANG KULIAH SAMBIL KERJA - Barkhowa, Mokhammad Khukaim Barkhowa; Auliya, Dina (UNPERBA, 2024)
Universities that offer courses to employees generally hold them outside of working hours, such as evening courses or weekend courses. Human resources are one of the key factors that companies focus on to meet job needs. The aim of this study seeks to examine the influence of work-study conflict and work-life balance on the work engagement of those studying while working in Salatiga City. This research was conducted on employees who study while working, the population of which is unknown. For a population whose size is unknown, the sample is a total of 16 indicators multiplied by 6, so the sample is 96 respondents. This type of research is quantitative with the data source being primary data and data collection using a questionnaire. The sampling technique uses simple random sampling. In hypothesis testing using multiple regression analysis, so that the resulting analytical model is declared good, it is necessary to test the validity, reliability, goodness of the model and classic assumption tests. The research results show that work study conflict has a negative and significant effect on work engagement, work life balance has a positive and significant effect on work engagement